2017
DOI: 10.1016/j.otsr.2016.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Results and limitations of humeral head resurfacing: 105 cases at a mean follow-up of 5 years

Abstract: IV, retrospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 25 publications
1
15
0
2
Order By: Relevance
“…Multiple definitions of overstuffing following RHA have been used in the literature including a medial deviation of the center of rotation [ 3 ], increased LGHO [ 19 , 20 ], and improper implant size [ 1 , 2 , 5 , 6 , 21 , 28 ], but little data exist on the reliability of these measurements. A recent study by Kadum et al investigated intra- and inter-observer agreement between four observers measuring LGHO on both computed tomography (CT) images and radiographs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Multiple definitions of overstuffing following RHA have been used in the literature including a medial deviation of the center of rotation [ 3 ], increased LGHO [ 19 , 20 ], and improper implant size [ 1 , 2 , 5 , 6 , 21 , 28 ], but little data exist on the reliability of these measurements. A recent study by Kadum et al investigated intra- and inter-observer agreement between four observers measuring LGHO on both computed tomography (CT) images and radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Resurfacing hemiarthroplasty (RHA) was developed to restore normal anatomy, and with a bone-preserving design and short operation time, it has often been preferred for the treatment of glenohumeral osteoarthritis [ 4 , 10 , 26 , 27 ]. Some studies have reported good functional outcome and a low rate of revision [ 14 16 , 22 , 23 , 28 , 31 ], while others report a poor functional outcome and a high risk of revision [ 7 , 8 , 10 , 11 , 17 , 24 ]. This has led to concerns that RHA may not adequately restore humeral anatomy [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 sólo 28 de las 50 prótesis evaluadas tenían un tamaño apropiado y este sobredimensionamiento puede condicionar un desgaste progresivo de la glena, como se ha publicado en varios trabajos. 21,22,23 La tasa de afl ojamiento parece mayor que con las prótesis con vástago 18,24,25 y el riesgo de fractura del cuello o el colapso de la cabeza humeral serían posibles complicaciones añadidas como ocurre en la resuperfi cialización de la cadera. 25,26 Utilizamos la escala de Constant normalizada para valorar la función obteniendo un valor promedio de 73 puntos.…”
Section: Discussionunclassified
“…Although Rai et al reported a revision rate of 4%, Levy et al reported a rate of 5-6% after 5-10 years[13]. Alizadehkhaiyat et al reported a revision rate > 20% at a mean follow-up of 4 years[14], whereas Soudy et al[15] reported a revision rate (surface replacement to reverse shoulder arthroplasty) of 17.5% (18/105 patients) after a mean follow-up of 43.6 months; the total revision rate was 23% (24/105 patients). Data from the Danish Shoulder Register show a cumulative revision rate of 14% for resurfacing hemiarthroplasty and only 2% for stemmed hemiarthroplasty after a mean of 5 years[16].…”
mentioning
confidence: 99%